2019
DOI: 10.3310/hsdr07200
|View full text |Cite
|
Sign up to set email alerts
|

Police-related triage interventions for mental health-related incidents: a rapid evidence synthesis

Abstract: Background Police officers are often the first responders to mental health-related incidents and, consequently, can become a common gateway to care. The volume of such calls is an increasing challenge. Objective What is the evidence base for models of police-related mental health triage (often referred to as ‘street triage’) interventions? Design Rapid eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…The unique characteristics of people with mental health who perpetrate violent behaviour may necessitate a targeted mental health response. One specific challenge in psychiatric care settings is that workers are often required to develop and maintain ongoing therapeutic relationships with patients (Rodgers et al , 2019). When health-care workers are required to maintain long-term therapeutic relationships with patients who behave aggressively this can be particularly challenging for their emotional and mental health (Jacob et al , 2020).…”
Section: Understanding Violence Within Complex Health-care Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The unique characteristics of people with mental health who perpetrate violent behaviour may necessitate a targeted mental health response. One specific challenge in psychiatric care settings is that workers are often required to develop and maintain ongoing therapeutic relationships with patients (Rodgers et al , 2019). When health-care workers are required to maintain long-term therapeutic relationships with patients who behave aggressively this can be particularly challenging for their emotional and mental health (Jacob et al , 2020).…”
Section: Understanding Violence Within Complex Health-care Systemsmentioning
confidence: 99%
“…Consistent with the idea of wicked problems, not all groups win together and small wins for certain groups can be overshadowed by damages to the aims of other groups (Termeer and Dewulf, 2019). As an example, a synthesis of evidence on police interventions for people with mental health challenges in the UK has shown that while having mental health professionals work with frontline police to attend to people in mental health crisis may increase the level of trust that people have in police, it may also have the potential to reduce the trust that is placed in those mental health professionals working with the police (Rodgers et al , 2019). There may be added difficulties when considering ways of managing wicked problems that are not politically expedient or in line with the broader ideological tenants of the government of the day (McConnell, 2018).…”
Section: Addressing the Complexity Of Violence In Health Carementioning
confidence: 99%
“…5 Due to limited resources, the only options available to police have been force and detention. 9 Section 136 (S136) of the Mental Health Act 1983 gives police authority to detain PMI in a safe place, often a cell, which can worsen the crisis. 9 10 Concerns about police capability to make decisions about people's mental health has led to changes in legislation and policy.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are concerns that FRs cannot provide expert support for PMI and report feeling ill-equipped 7 8. Limited training can result in inappropriate responses,5 9 for instance, tasers are more likely to be used during an MHC than a criminal arrest 5. Due to limited resources, the only options available to police have been force and detention 9.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation